Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Hasil Belajar IPS pada Siswa Kelas IX.3 SMPN 1 Masbagik - Muhamad, H. (MASALIQ, 2021)
This classroom action research is intended to determine whether the jigsaw type cooperative learning model can improve the learning outcomes of class IX.3 students of SMPN 1 Masbagik in the even semester of the 2020/2021 school year. This research was conducted in three processes, namely classroom observation, the implementation of the first cycle and the implementation of the second cycle. Starting from classroom observation to find out what initial steps are to be followed, the implementation of the first and second cycles is carried out, then it is investigated whether there is an increase in student learning outcomes after applying the jigsaw type cooperative learning model. Data on student work was analyzed using qualitative and quantitative methods with the aim of drawing conclusions about the effectiveness of this study. The results of this study showed an increase in classical completeness by 70% in the first cycle to 100% in the second cycle.